Odpowiedzi

2010-03-17T16:15:11+01:00
A)3×(a+b)×(b-2a)-2×(2a-b)×(a+3b)=3×(ab-2a²-b²+2ab)-2×(2a²+6ab-ba-3b²)=3×(3ab- 2a²-b²)-2×5ab+2a²-3b²=3×[3×(-1)×½-2×1-¼]- 2×[5×(-1)×½+2×1-3×¼=3×(-3¾)-2×(-⅝)=(-45/4)+(10/8)=(-90/8)+10/8=-80/8=-10

dla a=-1 , b=½

b)-4×(a+b)×(2a-3b)+2×(3a-2b)×9a+4b)=-4×(2a²-3ba+2ab-3b²)+2×(3a²+12ab-2ba-8b²)=-4×(2a²-ab-3b²)+2×(3a²+10ab-8b²)=-4×[2×4-(-2)×(-0,5)-3×(-0,5)²]+2×[3×(-2)²+10×(-2)×(-0,5)-8×(-0,5)²=-4×(8-1-0,25)+2×(12+10+2)=-4×6,75+2×24=-27+48+21

dla a=-2 , b=-0,5

Myślę że ci pomogłam
po znajomości dałabyś naj....xD
Pozdro!!!!
1 5 1